Spatial and temporal distribution of macrobenthos communities and their relationship with secondary front in Hangzhou Bay - Jia, Kangning; Tang, Yanbin; Liu, Qinghe; Zhang, Rongliang; Liao, Yibo; Shou, Lu; Zeng, Jiangning; Chen, Quanzhen; Chen, Jianfang (Frontiers in Marine Science, 2022)
Water quality in Hangzhou Bay is inferior (grade 5) because of discharged from Yangtze River and Qiantang River, and from factories around the bay. This study analyzed relationships between the environment and macrobenthic communities at 44 stations throughout Hangzhou Bay, based on samples collected in 2006, from 2016–2018, and in 2021. Long-term spatial and temporal changed in macrobenthos, and the influence of secondary water fronts on community composition, were discussed. Macrobenthos in Qiantang River Estuary was numerically, primarily dominated by crustaceans, and elsewhere by polychaetes. Species that differ most in abundance between four identified regions in the bay were the amphipod Corophium sinensis, clam Potamocorbula laevis, and polychaete Amaeana occidentalis. The abundance and biomass of macrobenthos in different regions differs significantly. Taxa were allocated to six feeding guilds: filter feeders and omnivores predominate in Qiantang River Estuary and south of Hangzhou Bay, while surface and subsurface deposit feeders predominate in sediments north of Hangzhou Bay and in the bay mouth area. Negative correlations were apparent between the abundances of polychaetes Nephtys polybranchia, Magelona japonica, Heterospio sinica, Sabella sp. and A. occidentalis and salinity and pH, while positive correlations were apparent between those of Sternaspis chinensis and Capitellidae indet. Fine-grained fraction (silt and clay) and mid-salinity were more suitable for macrobenthos. The numbers and biomasses of macrobenthic species in the Hangzhou Bay frontal area increased significantly relative to values in adjacent areas. The difference of each area near the front was more than 94%, and the main difference species were polychaetes and mollusks. Our baseline data for this region might ultimately contribute towards improved conservation of regional macrobenthos, and a better understanding of ecosystem health in this highly polluted bay.